One bold move a day : meaningful actions women can take to fulfill their leadership and career potential - Hocking, Shanna A. (McGraw Hill-Ascent Audio, 2022)
An essential roadmap to help women at every stage of their career feel stronger, more confident, and more intentional in their goals Even after being rejected 100 times right out of college, Shanna Hocking never strayed from her dream career and now, in One Bold Move a Day, you will benefit from lessons learned, and discover new, life-changing ways to build the confidence you need to succeed on your own terms. In One Bold Move a Day, Hocking shows how a single, measurable act each day provides the daily challenge that will help you truly grow. With insight gleaned from years in multi-billion-dollar nonprofits and running a business to support women leaders, Hocking offers actionable advice and useful tools to facilitate your personal journey. In chapters that range from "Lead from Where You Are" and "Invest in Yourself" to "Putting Your Bold Move Mindset to the Test," you'll discover how even the smallest step in the direction you want to go will help accomplish your biggest goals. Inside you'll find information on: Bold Mindset Shifts; how to lead from where you are; believing in yourself; Bold Move Performance Patterns; why progress is greater than productivity; networking, and involving others in your growth; communicating courageously and compassionately; showing up for yourself and others, and more